2021
DOI: 10.3389/fonc.2021.645008
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Rechallenge With BRAF and MEK Inhibitors in Metastatic Melanoma: A Further Therapeutic Option in Salvage Setting?

Abstract: BackgroundThe combination of BRAF and MEK inhibitors represents the standard of care treatment for patients with metastatic BRAF-mutated melanoma, notwithstanding the high frequency of emergent resistance. Moreover, therapeutic options outside clinical trials are scarce when patients have progressed after both targeted therapy and therapy with immune checkpoint inhibitors. In this article, we report our experience with targeted therapy rechallenging with BRAF and MEK inhibitors in patients with metastatic BRAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…The fourth patient currently on treatment with BRAF/MEK inhibitors showed clinical benefit and radiological stable disease for over 3 months. 17 Furthermore, the 5-year update of part 1 of the CO-LUMBUS trial further supports the use of combination treatment with BRAF and MEK inhibitors for advanced BRAF V600-mutant melanoma. This update demonstrated benefits in terms of progression-free survival and overall survival, reaffirming the role of this combination therapy as a standard of care.…”
Section: Discussionmentioning
confidence: 90%
“…The fourth patient currently on treatment with BRAF/MEK inhibitors showed clinical benefit and radiological stable disease for over 3 months. 17 Furthermore, the 5-year update of part 1 of the CO-LUMBUS trial further supports the use of combination treatment with BRAF and MEK inhibitors for advanced BRAF V600-mutant melanoma. This update demonstrated benefits in terms of progression-free survival and overall survival, reaffirming the role of this combination therapy as a standard of care.…”
Section: Discussionmentioning
confidence: 90%
“…In several preclinical studies performed using drug-naïve melanomas, various drug-tolerant subpopulations have been identified as a part of the response to BRAF V600 /MEK inhibition [33], including a subpopulation of MITF low /NGFR high cells [34][35][36]. While melanoma cell response to targeted therapeutics and their withdrawal after short exposure to drugs is a frequent subject of investigation (for example, [14,37]), reports on alterations induced by drug holiday and drug rechallenge in preclinical models of stable melanoma resistant to BRAF V600 /MEK inhibitors [18][19][20][21][22][23][24][25] or in melanoma patients who developed resistance [38][39][40][41][42][43][44] are limited. In this long-term study, we focused on two distinct trametinib-resistant melanoma cell lines exerting either a differentiation phenotype (MITF high ) or de-differentiation phenotype (MITF low ).…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, two recent phase II trials revealed worse progression-free survival in patients with melanoma treated intermittently with dabrafenib + trametinib or vemurafenib + cobimetinib compared with those treated with continuous therapy, with no difference in overall survival ( 38 , 39 ). On the other hand, retrospective and prospective studies of dozens of patients who progress on BRAF or MEK inhibitor have reported that more than one-third show a second clinical response after a drug holiday period ( 27 , 33 37 ). Preclinical studies using xenografts have been mixed as well.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies with patient-derived xenograft (PDX) melanomas or xenografts from established human melanoma cell lines showed that intermittent dosing can delay drug resistance and tumor growth compared with continuous dosing ( 29 32 ). Clinical reports and a phase 2 clinical trial have shown dozens of cases where patients with melanoma develop resistance and progress when treated with BRAF or MEK1/2 inhibitors continuously, but then show further response when retreated after a drug holiday period ( 32 37 ). By contrast, phase 2 trials of intermittent dosing with BRAF and MEK inhibitor combinations showed worse progression-free survival and no difference in overall survival compared with continuous treatment ( 38 , 39 ).…”
mentioning
confidence: 99%